Japan’s Defense Strategy : The Alternative for The Dynamic Asian Pasific - Yusep Ginanjar; Agus Subagyo; Akim Akim (Khazanah Sosial, 2020)
Since defense became a vital aspect in a sustainability of a country, its presence were inseparable from a policy-making process, especially foreign policy. A country needs a foreign policy to reach the national interest in keeping their existence due to respond several kinds of threats, or challenges in the international environment that was in an anarchic condition. Amidst the rivalries of many interests of various actors, Japan decided to make a change in their policy related with the defense strategy as the plan that Shinzo Abe proposed to finally allow Japan to be more offensive for some cases. As a research objective, this article will analyze how Japan defense policy framework developed from time to time, and mainly talk about how can Japan set aims in their own policy change from defensive to offensive by seeing internal and external factors. Therefore, there’ll be a link between how Japan run the policy as resolutions for several problems that arose surround Japan and prevented any harm or disturbance in national security, as the basic things to make sure the national interests are fulfilled. This research used qualitative method in analyzing the relevancy of internal and external factors towards Japan’s defense strategy, so that this research will contribute in the form of foreign policy analysis